Current measurement of engine oil with various gap length electrode - Benedick Conolius, Gabriel Addris (2016)
This thesis present about the conductivity of engine oil that exist when there is conductive particle involve in the viscosity of lubricant oil. Its also known as hydrocarbon particles. Experiment for voltage-current characteristic normally done by using electrode to detect the current or conductivity of lubricant oil. For this experiment, the gap length of electrode has been design from 1mm until 10mm. The electrode has been printed to PCB board so that easy to be conducted during experiment. Different kilometre of the sample lubricant oil has been collected after their utilization in transport system. There are two types of lubricant oil that being tested that are motorcycle’s and car’s lubricant oil. The high voltage DC supply will be connected to electrode. All the data obtained for each gap length of electrode has been recorded.